Finding a Work-integrated Learning Strategy that Enhances the Employability of Graduates of South African Universities of Technology: A Research Agenda - Jacobs, Henry; Dzansi, D.Y. (Journal of Economics, 2015)
A strategy refers to a plan to achieve a major goal. An important goal of South Africa’s Department of Higher Education (DHET) is to ensure that higher education institutions (HEIs) produce a steady flow of ‘ready for employment’ or ‘work-ready’ graduates. Universities of Technology (UoTs) offer a vocation-oriented curriculum. To prepare work-ready graduates, UoTs include a compulsory work-integrated learning (WIL) component in the curriculum. The expectation is that through WIL, learners will acquire the necessary practical experience to become ‘work-ready’ thereby enhancing the likelihood that they will be employed when they graduate. WIL is, therefore, a strategy for enhancing the learners’ employability graduation. WIL can be financially and nonfinancially demanding, therefore, UoTs have been searching for innovative ways to implement curricula in a costeffective manner without compromising quality and effectiveness. In this paper, the researchers outline a research agenda that can be used by South African UoTs to identify a sustainable WIL strategy.
Published Article
Keywords: Cooperative Education; Industry-engaged Learning; Internships; Apprenticeships; Experiential Learning; Work Ready; South Africa